Pengaruh Bauran Pemasaran, Psikologis Pengunjung, Pelayanan, Fasilitas, Keamanan, Sosial Dan Nilai Budaya Terhadap Keputusan Berkunjung Pada Objek Wisata Pantai Di Kota Padang (JURNAL ECONOMICA : Research of Economic And Economic Education, 2018)
This study aims to prove and analyze the influence of marketing mix, psychological factors, service, facilities, social, security and culture to the decision of tourists visiting the beach attractions in the Padang City. In this study the observation areas used include Padang Beach, Pasir Jambak Beach, Nirwana Beach, Karoline Beach and Sweet Water Beach. The number of samples used 160 tourists. The analysis model used is binary logistic regression. The test results showed that psychological factors, facilities and social significant effect on the decision of tourists visiting beach attractions in the city of Padang while marketing mix, service, security and cultural variables have no effect on the decision of tourists visiting beach attractions in the Padang city